Charismatic Christianity in Finland, Norway, and Sweden Case Studies in Historical and Contemporary Developments - Moberg, Jessica; Skjoldli, Jane (Springer Nature, 2018)
Pentecostal; Renewal; Televangelism; Scandanavia; Nordic